Primary Progressive Multiple Sclerosis: Putting Together the Puzzle - Abdelhak, Ahmed; Weber, Martin S.; Tumani, Hayrettin (Frontiers in Neurology, 2017)
The focus of multiple sclerosis (MS) research has recently turned to the relatively rare and clearly more challenging condition of primary progressive (PP)-MS. Many risk factors such as genetic susceptibility, age and EBV infection may interdepend on various levels, causing a complex pathophysiological cascade. Variable pathological mechanisms drive disease progression, including inflammation-associated axonal loss, continuous activation of CNS resident cells, such as astrocytes and microglia as well as mitochondrial dysfunction and iron accumulation. Histological studies revealed diffuse infiltration of the grey and, white matter as well as of the meninges with inflammatory cells such as B-, T-, natural killer- and plasma cells. While numerous anti-inflammatory agents effective in relapsing-remitting MS basically failed in treatment of PPMS, the B-cell-depleting monoclonal antibody ocrelizumab recently broke the dogma that PPMS cannot be treated by an anti-inflammatory approach by demonstrating efficacy in a phase 3 PPMS trial. Other treatments aiming at enhancing remyelination (MD1003) as well as EBV-directed treatment strategies may be promising agents on the horizon. In this article, we aim to summarize new advances in the understanding of risk factors, pathophysiology and treatment of PPMS. Moreover, we introduce a novel concept to understand the nature of the disease and possible treatment strategies in the near future.